Diversity‐multiplexing tradeoff in MIMO radars. Issue 4 (1st April 2017) - Nazari Majd, Mohammad; Radmard, Mojtaba; Chitgarha, Mohammad Mahdi; Farina, Alfonso; Nayebi, Mohammad Mahdi; Bastani, Mohammad Hasan
Abstract : Two gains play key roles in recently developed multiple‐input–multiple‐output (MIMO) wireless communication systems: 'spatial diversity' gain and 'spatial multiplexing' gain. The diversity gain (DG) refers to the capability to decrease the error rate of the MIMO channel, whereas the multiplexing gain (MG) implicitly refers to the amount of increase in the capacity of the MIMO channel. It has been shown that there is a fundamental tradeoff between these two types of gains, meaning interplay between increasing reliability (via an increase in the DG) and increasing data rate (via an increase in the MG). On the other hand, recently, MIMO radars have attracted much attention for their superior ability to enhance the system's performance. As an MIMO system, it is expected that the mentioned diversity‐multiplexing tradeoff exists in an MIMO radar, too. In this study, first, these two gains are obtained in an MIMO radar system in a closed‐form solution. The authors have shown that the DG of an MIMO radar is directly related to its detection performance and the MG represents its capability in estimating the target's parameters. Finally, the tradeoff between these two gains in an MIMO radar is studied and verified theoretically and through simulations.